DESIGN AND IMPLEMENTATION OF FACE TRACKING SYSTEM USING VIOLA JONES AND TEMPLATE MATCHING METHODS FOR PAN-TILT SYSTEM WITH LEAD-LAG AND PID CONTROL - YOSAFAT SARAGIH - NIM : 23214331, ROBIN
Tracking design and implementation equipped with pan-tilt system are presented in this thesis for tracking a face continuously in order that it is always located in the frame window. A camera is used as a visual sensor for capturing and obtaining the actual position of the face object. Viola Jones algorithm is used to detect the presence of the face and template matching algorithm acts as a back-up if Viola Jones fails to detect. To keep the face object is always located in the center of the frame and able to be tracked automatically, lead-lag compensator algorithm and PID are constructed by comparing detected face coordinates with center frame coordinates. Therefore, modelling system is required to obtain pan-tilt system transfer function to be used in designing lead-lag compensator. Meanwhile, PID parameters are tuned by using second Ziegler Nichols method. Both controller algorithms are then compared and analyzed in accordance with system specification design. Overall, experimental results show that PID has faster transient response than lead-lag either for pan or tilt.